2001
DOI: 10.1021/ja004312d
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Regulated Nanospace around a Porphyrin Core

Abstract: A series of 1,3,5-phenylene-based rigid dendritic porphyrins were synthesized by Suzuki coupling between a porphyrin core and dendron units. The intramolecular energy transfer was studied by absorption and fluorescence spectroscopies. The encapsulation of the porphyrin core within the 1,3,5-phenylene dendron units was found to provide highly efficient energy transfer from the dendron units to the porphyrin core. The dendritic wedge structure affected the energy transfer efficiency. The 1,3,5-phenylene-based ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 62 publications
(31 reference statements)
1
62
0
Order By: Relevance
“…In this respect, Kimura et al [68] have synthesized 1,3,5-phenylene-based rigid dendritic porphyrins with well-defined nanospaces formed around the porphyrin core that provide cavities for inclusion of C 60 . In addition, the dendritic porphyrin moiety interacts strongly with C 60 through π-donor/π-acceptor interactions, leading to a very good stability of the complex in toluene.…”
Section: Porphyrinementioning
confidence: 99%
“…In this respect, Kimura et al [68] have synthesized 1,3,5-phenylene-based rigid dendritic porphyrins with well-defined nanospaces formed around the porphyrin core that provide cavities for inclusion of C 60 . In addition, the dendritic porphyrin moiety interacts strongly with C 60 through π-donor/π-acceptor interactions, leading to a very good stability of the complex in toluene.…”
Section: Porphyrinementioning
confidence: 99%
“…Porphyrins were selected as core molecules because of their potential applications in many areas [156][157][158][159]. Reports dealing with porphyrins decorated with dendrimers had previously appeared [112,[160][161][162][163][164][165][166][167][168]. After investigating three different synthetic strategies for this study, it was concluded that a spacer was required to be attached to the porphyrin to increase the hydrolytic stability and allow synthesis of higher generations.…”
Section: 15mentioning
confidence: 99%
“…Thus, pyrene is a fascinating core for constructing fluorescent-conjugated light emitting dendrimers. In addition, several types of chromophoric dendrimers backbone such as polyphenylene (Gong et al, 2001;Xu et al, 2002;Kimura et al, 2001), poly(phenylacetylene) (Xu  Moore, 1993;Meliger et al, 2002), and poly(benzyl ether) (Jiang  Aida, 1997;Harth et al, 2002) have been widely used as light absorbers, and the energy was efficiently funnelled to the core accepter. In this section, we presented the synthesis and photophysical properties of pyrene-cored light-emitting dendrimers that have been investigated for the preparation of optoelectronically active solution-processable light emitting dendritic materials and concentrate on the potential applications in OLEDs, in www.intechopen.com www.intechopen.com which some light emitting dendrimers have been used.…”
Section: Functionalized Pyrene-based Light-emitting Dendrimersmentioning
confidence: 99%